HUBUNGAN PENDIDIKAN, KONSELING, PEMBERIAN MAKANAN TAMBAHAN (PMT) DENGAN STATUS GIZI BALITA DI PUSKESMAS TELUK KARANG KOTA TEBING TINGGI - Evawani Martalena Silitonga; Donal Nababan Nababan; Frida Lina Tarigan; Vivia Ningsih; Mido Ester J. Sitorus (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Lack of nutritious food will cause stunted growth of children and excessive food is also not good because it causes obesity. Adequacy of feeding children is very important because lack of energy/nutrients can interfere with optimal growth, and can also cause nutritional disorders, both curable or not. This study aims to determine the relationship between maternal education, counseling and supplementary feeding on the nutritional status of children under five. This study used a cross-sectional design. The research population was all mothers of children under five who were in the Teluk Karang Health Center in the city of Tebing Tinggi in 2021. The research sample was 56 people obtained by accidental sampling technique. Data was collected by distributing questionnaires to mothers of children under five. Â The data processing process starts from editing, coding, entry, cleaning and tabulating. Analysis of research data consisted of univariate and bivariate analysis with chi square test, multivariate with logistic regression test. The results showed that there was a relationship between maternal education (p=0.010), counseling (p=0.004; PR=2,3;95%CI 1.245-4.588), supplementary feeding (p= <0.001; PR=3.6;95 %CI 1.758-7.417) with the nutritional status of children under five. The results of multivariate analysis showed that the dominant variable related to the nutritional status of toddlers was the provision of additional food (p = <0.001; PR = 7.5; 95%CI 3.768-64.441), meaning that toddlers who did not get additional food had 7.5 times the tendency to experience nutritional status is not normal compared with toddlers who get additional food. Thus, mothers of toddlers should actively visit the puskesmas and often consult with doctors, nurses and nutritionists regarding the foods needed by children under five to obtain normal nutritional status.Â Â